Configuring Local Food Resources into Youth-Centered Entrepreneurship in Rural Indonesia - Dwi Aryanthi; Rokhani Hasbullah; Popong Nurhayati; Elisa Anggraeni (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Rural youth increasingly distance themselves from local resource-based enterprises, even where valuable food commodities and development programs exist. Local food resources offer entrepreneurial potential that does not automatically translate into youth participation. This study examines how local food resources are configured into youth-centered entrepreneurship through business model configurations rather than treated as commodities for direct commercialization. Using a qualitative comparative case study of hanjeli-based initiatives in Waluran, Sukajadi, and Bedono, the study analyzes interviews, Business Model Canvas documentation, and field materials through BMC-based coding, within-case analysis, cross-case comparison, and abductive synthesis. Three configurations emerge. Waluran develops an experience-based pathway through educational tourism, ecological learning, and market-facing products. Sukajadi forms a community food pathway through collective processing, farmer linkage, and consumer education. Bedono advances a norm-based pathway through seed recovery, food heritage, and consumption routines. The findings show that rural markets are socially formed through experience, education, trust, and norms, while youth-regeneration value appears uneven across configurations. Sustainability depends on vulnerability management, organizational capacity, and community legitimacy. The study contributes to the rural entrepreneurship literature by reframing local food resources as business model configurations that create economic, social, ecological, and regenerative value for rural youth.